Analysis of the epic "Bersisi Abed" for poet "Faqi Tayran" according to Grimas Theory - Mohammad, Sheelan Y.; Mohammad, Abdi H. (Humanities Journal of University of Zakho, 2019)
Narrative science through a new and structuralist vision attempt to analyze the structure of narrative text. Narrative science and according to the language of the story, narrative grammar and the system controlling all types of narrative science. Grimas as one of the founders of the narrative science worked by facilitating a model of thirty-one roles for (Brob) on six roles under the title of events. Through this theory, the events of the character and the role of the frequency of the narrative, he tried to explore the law and rules of the narrative. A characteristic of Grimas' theory is its compatibility with all narrative texts. In this paper, an attempt was made to analyze some models of the epic “Bersesi Abed” according to Grimas' theory. The epic "Baresisi Abed" is one of the long and famous poetry stories of (Faqi Tayran) and one of the stories full of human conflict, desire and faith.